Pemanfaatan Teknologi Location Based Service (LBS) dalam Pengembangan Sistem Presensi Guru (Studi Kasus: SMPN 8 Malang) - Anisa Dwi Novita Rika; Issa Arwani; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Teacher attendance system is a teacher attendance documentation that is useful for monitoring teacher attendance every day. During this time, the teacher attendance system applied at SMPN 8 Malang is only a daily attendance system. Teacher attendance system for each subject still doesn't exist, this results in monitoring staff not easily monitoring teachers who are teaching. From these case, it is necessary to develop a teacher attendance system on Android-based that is equipped with location and photo features for each subject to facilitate the teacher monitoring process. To add authentic evidence class leaders can send photos and review lessons. Photos can only be taken in realtime. The location feature utilizes Location Based Service technology to determine the location of teachers and class leaders who are within the radius of the school in order to make a presence. The system will automatically send alpha status to teachers who are not doing presence using scheduling on cron jobs. The teacher attendance system was developed using the System Development Life Cycle development method using the waterfall model because the manufacturing is done in stages. The test results of the System Usability Scale (SUS) obtained 87 which states that the teacher attendance system is included in the category of acceptable with the best imaginable adjective rating, so it can be said that the teacher presence system can be well received by users.